A importância da motivação nas decisões proferidas no processo individual do trabalho no Brasil - Guimarães, Ricardo Pereira de Freitas (2006)
The dissertation we proposed to develop is sustained on the impor-tance of motivation for decisions made by Judiciary on the scope of individ-ual process of national labor, watched from a inner angle of the process, on the optics of the own parts, the society en the principles. This study has fol-lowed the rule of obedience to judicial decisions to the Constitution s article 93, IX, followed by doctrinal and jurisprudential research found about the theme, involving constitutional process principles and the ones specific to individual labor process subject, looking for finding the logics of insertion on national Law of obligation of decisions basement, considering the hard work addressed to Judiciary of pointing out the motivation of their own decisions, case by case